Komunikasi Interpersonal Antara Pihak Sekolah Dan Orang Tua Siswa Dalam Keaktifan Siswa Setelah Pandemi Di Sekolah It Daarul Istiqlal - Yolanda, Agnita; Nurismilida, Nurismilida; Sari, Ruri Aditya (CV. Utility Project Solution, 2023)
After the Covid-19 Pandemic has passed, people can be free to carry out their daily activities as usual. The current conditions certainly make it easier for the community, especially for parents, where when the Covid-19 Pandemic hit Indonesia, parents also took on the role of teacher or tutor when children studied at home. With the existence of guidelines that refer to the online learning system in the Minister of Education and Culture Decree Number 4 of 2020 which contains all the mechanisms of the school learning system, that only exams or tests held in face-to-face processes are not allowed to be carried out, but are replaced with online or virtual systems through existing internet network or technology. The purpose of this study was to find out the form of interpersonal communication between the school and parents of students in student activity after the pandemic. This type of research uses a qualitative approach. Interpersonal communication between the school and parents is open in communicating to find out firsthand what problems are being experienced by students, teachers, and other school members. After the pandemic, the process of interpersonal communication that occurred between the school and parents was carried out face to face. In effective communication, of course, the role/support of parents is very important in the development of students which will then be further developed by the school/teacher.